2020
DOI: 10.1177/1367493520942711
|View full text |Cite
|
Sign up to set email alerts
|

Online assessment of problem-solving skills among fathers of young and school-age children with type 1 diabetes: Associations with parent and child outcomes

Abstract: Type 1 diabetes (T1D) is a pediatric chronic illness that is associated with significant parenting stress due to its lifelong course, burdensome disease management, and life-threatening complications. Although mothers of children with T1D have been studied extensively in relation to parenting stress, coping, and diabetes outcomes, there is a need to examine similar variables among fathers. The aim of the present study was to examine if fathers’ use of problem-solving skills was related to parenting stress and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
(74 reference statements)
1
2
0
Order By: Relevance
“…Our findings additionally showed an association between higher HbA1c and lower household income in univariate analysis, which is consistent with prior research [58,59]. Last, in the bivariate associations, lower paternal education level was linked with higher HbA1c, which is consistent with research suggesting that both parental education and the father's engagement and problem-solving ability in diabetes management are beneficial for children with type 1 diabetes [7,[60][61][62].…”
Section: Associations Of Parent Neuroticism and Child Effortful Contr...supporting
confidence: 91%
“…Our findings additionally showed an association between higher HbA1c and lower household income in univariate analysis, which is consistent with prior research [58,59]. Last, in the bivariate associations, lower paternal education level was linked with higher HbA1c, which is consistent with research suggesting that both parental education and the father's engagement and problem-solving ability in diabetes management are beneficial for children with type 1 diabetes [7,[60][61][62].…”
Section: Associations Of Parent Neuroticism and Child Effortful Contr...supporting
confidence: 91%
“…Participants were 344 North American fathers of children ages 2–10 years with type 1 diabetes (T1D). These participants were taken from two previous studies that investigated parenting stress and coping skills in fathers of children with T1D (Teasdale & Limbers, 2018, Teasdale & Limbers, n.d.). Table 1 provides demographic information for the fathers and children in the current sample.…”
Section: Methodsmentioning
confidence: 99%
“…A detailed description of the study procedures can be found in the two previous studies the sample was taken from (Teasdale & Limbers, 2018, Teasdale & Limbers, n.d.). Inclusion criteria for the present study included being English literate, 18 years or older, and a father with a child 2–10 years old diagnosed with T1D by a physician (who resided at least 50% of the week with the father).…”
Section: Methodsmentioning
confidence: 99%